Peran Serta Masyarakat dalam Pengelolaan Lingkungan Hidup di Kelurahan Sepatan - Siregar, Indra Gunawan Siregar; Furqon, Wahyul; Rosidi NH, Imron; AR, Khorida; Fahreja , Mohamad Rizky Fahreja (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This Community Service (PKM) activity was carried out by lecturers and students with the aim of increasing public awareness in environmental management through understanding and implementing relevant Regional Regulations (PERDA) that apply in Sepatan Village, namely Tangerang Regency PERDA number 1 of 2023. The main problem faced was the low level of community participation in preserving the environment, caused by a lack of understanding of the regulations and minimal outreach regarding the legal consequences and collective benefits of complying with PERDA. The activity implementation methods included outreach, group discussions, and direct community mentoring. Outreach aimed to provide an understanding of the contents of PERDA on the environment, while group discussions encouraged interaction and the exchange of experiences among residents in implementing these regulations. The mentoring focused on simple practices, such as household waste management, reforestation, and reducing the use of single-use plastics. The results of the activity demonstrated increased public knowledge of environmental laws and a growing collective awareness to play an active role in maintaining environmental cleanliness and sustainability. Furthermore, this activity also fostered a shared commitment to supporting the sustainable implementation of PERDA. Thus, this PKM emphasizes that regional regulations (PERDA) can function as an effective educational and regulatory instrument to build public awareness and participation in environmental management.